PENERAPAN MODEL PEMBELAJARAN BERBASIS NILAI (VALUE-BASED LEARNING) DALAM PEMBELAJARAN PAI DI KELAS PGSD A1 - Rouhdotul Kholilah; Nasrul Syarif; Mavatih Fauzul ‘Adziima (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to describe the application of a value-based learning model (VLB) in the Islamic Religious Education (PAI) course in the PGSD A1 class. This model is based on Value Education Theory which emphasizes the internalization of moral and spiritual values in the learning process. Through reflective discussion methods and case analysis of Islamic values, this study seeks to develop students' understanding of religious and social values. The research subjects were 47 PGSD A1 class students, consisting of 44 Muslim female students, 1 non-Muslim female student, and 2 Muslim male students. The learning outcomes show that the value-based approach is effective in fostering religious, tolerant, and reflective attitudes towards value diversity in the classroom environment.